O povo fez sua santa: canonização espontânea nas narrativas dos devotos de Mártir Francisca de Aurora - Morais, Álvaro Dellano Rios (2008)
This study intends to understand how a process of “spontaneous canonization” works, in the context of Brazilian religiosity. The idea of Paul Zumthor defines a sociological phenomenon in which persons (alive, dead or imaginary ones) are taken as saints by the people, but they aren’t recognized by the Catholic Church as saints. The object of this research is the case of Martyr Francisca, a popular saint whose cult is located in Aurora (Ceará - Brazil). The study focuses on narratives that reconstruct the history of the martyr, analyzing spoken and written sources. When she was 16, Francisca Augusta da Silva was murdered by her ex-groom, in 1958. Where she fell dead, the people of Aurora built a small chapel. This chapel attracted believers who search helping from the saint of Aurora.